2011
DOI: 10.1016/j.tem.2010.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Lipoexpediency: de novo lipogenesis as a metabolic signal transmitter

Abstract: De novo lipogenesis, the production of fats from simple precursors, is often dismissed as irrelevant to the pathobiology of obesity caused by positive energy balance due to typical high fat diets. However, emerging data implicate de novo lipogenesis in the generation of metabolic signals that alter disease risk. Exploiting this signaling pathway represents lipoexpediency. Lipoexpediency is the concept of directing fats toward benefit even in the setting of lipid overload, and represents a strategy to complemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
109
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(115 citation statements)
references
References 71 publications
(71 reference statements)
5
109
0
Order By: Relevance
“…In agreement with this concept, an identified population of obese humans can stay free of insulin resistance and are metabolically healthy despite morbid obesity (12). These findings suggest that not all lipids are detrimental for insulin sensitivity and that specific lipid species, when present in the proper location and time, may trigger signals that modulate adaptation to stress (13,14).…”
Section: Introductionmentioning
confidence: 82%
“…In agreement with this concept, an identified population of obese humans can stay free of insulin resistance and are metabolically healthy despite morbid obesity (12). These findings suggest that not all lipids are detrimental for insulin sensitivity and that specific lipid species, when present in the proper location and time, may trigger signals that modulate adaptation to stress (13,14).…”
Section: Introductionmentioning
confidence: 82%
“…(Enser et al 2000;Bell et al 2001;Benatmane et al 2011), but only few data on its effect on poultry liver have been found. As we know, liver is the major site of lipogenesis and de novo fatty acid biosynthesis (Lodhi et al 2011), and liver lipid transfer to other tissues through blood and exerting effect on the lipid content and composition. So further research into the effect of dietary fat source on the fatty acid deposition in poultry liver is needed to understand the mechanisms underlying the deposition of PUFA in poultry tissues (muscles, abdominal fat, and eggs).…”
Section: Introductionmentioning
confidence: 99%
“…While it is considered to be quantitatively minimal by some ( 6, 7 ), others have demonstrated that DNL-derived lipids can negatively impact metabolic health and contribute to hepatic steatosis and visceral adiposity in humans ( 8-10 ). Of particular importance in the context of whole-body metabolic homeostasis, recent evidence suggests that de novo synthesized fatty acids and lipids serve important signaling and regulatory roles in cellular and systemic metabolism ( 7,11 ).MUFAs are major components of tissue lipids such as TGs, cholesteryl esters (CEs), and GPs , and high levels of MUFAs are inversely associated with metabolic health. The stearoyl-CoA desaturase (SCD) family of enzymes catalyzes the synthesis of MUFAs by insertion of a cis double bond at the ⌬ 9 position of saturated fatty acids.…”
mentioning
confidence: 99%
“…While it is considered to be quantitatively minimal by some ( 6, 7 ), others have demonstrated that DNL-derived lipids can negatively impact metabolic health and contribute to hepatic steatosis and visceral adiposity in humans ( 8-10 ). Of particular importance in the context of whole-body metabolic homeostasis, recent evidence suggests that de novo synthesized fatty acids and lipids serve important signaling and regulatory roles in cellular and systemic metabolism ( 7,11 ).…”
mentioning
confidence: 99%